The Mystical Presence of Christ by Richard Kieckhefer | Hardcover (Cornell University Press)
The Mystical Presence of Christ investigates the connections between exceptional experiences of Christ's presence and ordinary devotion to Christ in the late medieval West. Unsettling the notion that...